Technical efficiency of orange growers in the agro industry in São Paulo: A case study - de Freitas, Maria Gabriela [UNESP]; Sabbag, Omar Jorge [UNESP] (My University, 2021)
In the productive environment, it is relevant to assess the technical efficiency of orange suppliers and quantify the returns to the productive scale, in addition to proposing an action plan for a better use of inputs on properties and actions aimed at gains in the production cycle and competitiveness in the sector. This paper aimed, through a case study, to evaluate the technical productive efficiency of orange producers that supply the agroindustry. Methodologically, the research was quantitative, descriptive and exploratory, applied to six variables (five inputs and one product), with the help of the DEAP 2.1 software, through the feedback of twenty interviews carried out with producers during the 2018/2019 harvest. The results show that the overall average efficiency obtained among the analyzed production units was 69.8%, with 30% of the producers having 100% efficiency and 45% having efficiency above 80%. The inputs production area and labor were the ones that most influenced the efficiency of the analyses. The mapping of the variables of the productive environment of the surveyed producers made it possible to scale the analysis of the technical efficiency of the fruit delivered for processing in the agroindustry, as well as identifying points for improvement, guiding producers to adopt more assertive practices and strategies that address the development and they generate competitiveness. It is concluded that the present study contribute to align the strategies of input use in citrus properties, with the possibility that, eventually, that the best properties are used as competitive benchmarking for the sector.
Keywords: Citriculture; DEA analysis; Performance